UiTM Environmental Sustainability Report 2021 - 2022 - UiTM, UGC (UiTM Green Centre, 2021)
The Universiti Teknologi MARA Environmental Sustainability Report (ESR) 2021/2022 is part of the UiTM Green Centre (UGC) deliverables from the ideation of UiTM Greenation Strategic Plan. With the theme “Greening UiTM”; the UiTM ESR 2021 summarizes the overall progress in university and camps sustainability initiatives which aim to be associated with the UGC Core Area – Ui Green Metric (UiGM) and Low Carbon Challenge (LCC) through the year of 2021. This report presents information on sustainable initiatives undertaken by UiTM in its main as well as branch campuses throughout the country. The UiTM community comprehensively visualizes UiTM sustainability endeavors in times of the COVID-19 pandemic crisis and continuously manages it well during the post pandemic. More importantly, the UiTM community has created value through the sustainability perspectives as envisioned via the 17 Sustainable Development Goals (SDGs) and UiTM Strategic Planning 2025. UiTM has sustained and accelerated various initiatives to adapt to these changes. This progress is an opportunity for UiTM to seek thoughtful partners which supportively strategize to learn and co-create innovative planning to solve sustainability challenges in the campus, nation, and global scale.